PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PUBLIK PADA KANTOR KECAMATAN MENGGALA KABUPATEN TULANG BAWANG - Asmaria Asmaria; M Fikri Akbar; Mey Ningsih Marbun (Universitas Bandar Lampung (UBL), 2021)
The essence of local government in an area is to provide services to the community both in terms of quality and quantity, which means that the government as a public servant is required to